Perception of English for Scientific Purposes (ESP): Experential and Impact Perceived by Non-English Department Students - Pehala, Ilfan Askul; Zur, Sarjaniah (Universitas Pendidikan Ganesha, 2025)
Non-EFL students frequently encounter challenges in understanding and applying the English for Scientific Purposes (ESP) taught in the first year of university. This problem provokes questions regarding the extent to which ESP meets students' academic and professional needs, as well as its relevance to the curriculum and the demands of the working world after they graduate. This study aims to explore students' perceptions of the implementation of ESP in this context, and to critically assess its effectiveness and impact. This qualitative research uses reflection and semi-structured interviews as its instruments. The participants in this study were 77 students who were enrolled in different study programs across four faculty. Data obtained from participants' answers and responses were analyzed using thematic analysis.The result indicate that students generally perceive a strong connection and correlation between ESP and the curriculum, scince, and professionalism. In addition, this study also revealed students' experiences during ESP, the influence they perceive, and the contribution of ESP to their academic development. This finding imply that, closer collaboration between lecturers, study programs, and students is recommended to ensure that ESP is not only theoretical, but also has a sustainable practical impact and is relevant to the needs of the working world. The ESP taught should focus on the relevance of the course to the major and study program, while also enhancing students' proficiency in producing scientific articles that are suitable for publication.